Parameters Affecting Coating Uniformity for Geopolymer Coated Fertilizer - Nik Azharuddeen, Nik Muhammad Harris (IRC, 2015)
The establishment of Control Release Fertilizers (CRF) in agriculture industry has given great significant outcome towards the development of economy while preserving the environment. As it is developed through coating process, it is not only help to increase fertilizer’s efficiency, but also minimize the loss of nutrients into soil and environmental pollution. There are many types of coating materials that have been used and studied extensively in everyday life such as in road construction and corrosion control of steel structures like offshore platforms. For this research, the geopolymer composite material has been developed and is introduced as the main coating material for the CRF. Geopolymer material is much more environmental friendly compared to sulphur and polymer based. However, the combination of fly ash-based powder, sodium hydroxide (NaOH) solution, and distilled water producing this geopolymer material needs further research to ensure it is clearly suitable to be used as coating material. Coating uniformity of urea fertilizer is critical to allow urea to be released at controllable time with steady rate. It will also affects the rate of which the nutrients will be released. Better wettability properties of a geopolymer droplet from its solution promotes thin-film formation on urea fertilizers surface. Therefore, certifies the uniformity in coating process. Three parameters have been studied for this research to identify its effect towards the coating uniformity of geopolymer material on the surface of urea granules. They are inlet air pressure, rate of spraying and dry holding time. A method has been implemented by spraying the urea sample with geopolymer slurry with respect to its variability of inlet pressure, spraying rate and drying time. The spraying process is repeated for 25 times before the sample is put curing. Low pressure and low spraying rate has been identified to produce optimal size of coated sample with average thickness of 200 μm all over the granule. Air inlet pressure at 0.3 bar, spraying rate at 30 rpm and 3 minutes of dry holding time have been identified to be the most ideal parameters that is used to produce coated urea with coating uniformity